2010
DOI: 10.1016/j.resmic.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

U(VI) reduction by spores of Clostridium acetobutylicum

Abstract: Vegetative cells of Clostridium acetobutylicum are known to reduce hexavalent uranium (U(VI)). We investigated the ability of spores of this organism to drive the same reaction. We found that spores were able to remove U(VI) from solution when H 2 was provided as an electron donor and to form a U(IV) precipitate. We tested several environmental conditions and found that spent vegetative cell growth medium was required for the process. Electron microscopy showed the product of reduction to accumulate outside th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…U precipitates also appear in close proximity to the exosporium-like surface, the outermost shell surrounding the mature spore ( Fig. 5F and S4); this proximity is consistent with what Dalla Vecchia et al (2010) observed in batch tests of U(VI) reduction by spores of Clostridium acetobutylicum.…”
Section: 3supporting
confidence: 88%
“…U precipitates also appear in close proximity to the exosporium-like surface, the outermost shell surrounding the mature spore ( Fig. 5F and S4); this proximity is consistent with what Dalla Vecchia et al (2010) observed in batch tests of U(VI) reduction by spores of Clostridium acetobutylicum.…”
Section: 3supporting
confidence: 88%
“…These include reductive precipitation by outer membrane cytochromes, conductive pili, or spores (6)(7)(8)(9)(10), surface adsorption by exopolysaccharide (EPS) or S-layers (9,11), or precipitation with phosphate (4,5,12,13). However, mechanisms used by cells for combating internal U toxicity are poorly understood (14).…”
mentioning
confidence: 99%
“…Recently, a study has reported that spores of C. acetobutylicum DSM 792 can carry out reduction of U (138).…”
Section: Clostridium Acetobutylicummentioning
confidence: 99%
“…4). Using X-ray absorption near edge structure (XANES), Vecchia et al (138) verified that the product of U reduction was U(IV) instead of U removal being due to U(VI) precipitation or adsorption.…”
Section: Clostridium Acetobutylicummentioning
confidence: 99%
See 1 more Smart Citation